ALMA PIEDOSA, CORPO SÃO: O PAPEL DA DEVOÇÃO NA CURA DAS DOENÇAS NO BRASIL COLONIAL - Viotti, Ana Carolina De Carvalho [UNESP]; Santos, Clara Braz Dos [UNESP] (Universidade Federal de São Paulo - UNIFESP, 2020)
The belief that bodily health was closely tied to the virtues of the soul was a shared topic among clerics, religious, moralists - also among physicians -, which was why treating the ills of the flesh from the medicines for the spirit was not uncommon in Portuguese America throughout the colonial period, especially in the 18th century. Among the many “remedies” that could be applied to those sick bodies and sinful souls, claiming for the help of the saints can be highlighted as the most effective strategy, and books such as the Botica preciosa e thesouro precioso da Lapa, written by the missionary Ângelo de Siqueira (1707-1776) and published in 1756, became more and more usual. This study will examine the writings produced by a series of Catholic scholars who, in instructing the devotee, prescribed, as Siqueira, the best ways to preserve or re-establish the health of spirit and body.

A crença de que a saúde do corpo estava intimamente atrelada às virtudes da alma fez-se premissa entre clérigos, religiosos, moralistas - e também entre médicos -, razão pela qual tratar os males da carne a partir de medicamentos para o espírito não foi incomum na América Portuguesa ao longo do período colonial, especialmente no século XVIII. Dos muitos “remédios” que poderiam ser aplicados àqueles corpos doentes e às almas pecaminosas, o recurso aos santos salta aos olhos como o mais eficaz, e obras como a Botica preciosa, e thesouro precioso da Lapa, escrita pelo missionário paulista Ângelo de Siqueira (1707-1776) e publicada em 1756, passam a ser cada vez mais usuais. Neste estudo, serão perscrutados os escritos produzidos por uma série de letrados católicos que, ao instruir os fiéis, prescreviam, a exemplo de Siqueira, as melhores formas de conservar ou reestabelecer, ao mesmo tempo, a saúde do espírito e do corpo.
PIOUS SOUL, HEALTHY BODY: THE ROLE OF DEVOTION IN THE CURE OF THE DISEASES IN COLONIAL BRAZIL
Keywords: Devotion; medicine; colonial Brazil; Devoção; medicina; Brasil colonial